Development of Web-Based Physics Learning E-Modules to Improve Science Literacy - Roli Rike Karnando; Sugiarti Sugiarti; Lefudin Lefudin (Universitas Lambung Mangkurat, 2023)
This study aimed to develop a web-based physics learning e-module using the content management system WordPress to help improve the science literacy of SMA Negeri 4 Empat Lawang students for the 2022/2023 academic year. The background of the problem in this study is in the form of low science literacy caused by the lack of variations in the use of other learning resources used by teachers during the learning process; teachers only use printed books provided by schools as learning resources, in addition to using methods in learning. Also, they only use the conventional lecture method, which tends to attract students' attention and has been going on for approximately the last three years. This type of research used a research and development method or Research and Development with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), then for the evaluation stage using formative evaluation, according to Tessmer. The population for this study consisted of 43 students consisting of 13 students in the one-to-one and small group stages, and 30 other students for the evaluation stage. The results of this development are e-modules that have been validated by experts and are declared valid with an average of 84.9%. Then, the e-module developed was also declared practical with an average score of 78.9% in the one-to-one and small group stages. And for the effectiveness of the developed e-module, it got an N-gain score of 0.70 for increasing students' science literacy in the high category.